Coetzee & co: failure, lies and autobiography. Issue 3 (15th April 2016) - Sheehan, Paul
Abstract : The most recent critical studies of J. M. Coetzee's oeuvre have paid little attention to the writer's autobiographical fictions, either downplaying their importance or ignoring them altogether. In this essay I make a case for the their formal and thematic significance. Focusing principally, though not exclusively, on the Scenes from Provincial Life (2011), I demonstrate how this trilogy of works is written against the generic impositions of life-writing. Those impositions turn on the notion of triumphalism: every memoir, auto/biography, confessional narrative, and so on, implicitly or explicitly affirms a teleology of achievement, in showing how the self-reflecting subject becomes a self-writing subject capable of narrating its own development. Coetzee's auto-fictions, by contrast, stage a kind of agon with this generic demand by focusing on failure, on solipsistic distraction, and on the nature of belonging. In addition, and following clues from Coetzee's unpublished notebooks, I suggest that the spurs for these textual reworkings can be found in French literature – in particular, the auto-fictive writings of Roland Barthes and Alain Robbe-Grillet. The Scenes are finally shown to be not only central to Coetzee's wider novelistic concerns, but also to his ethics of the outsider and the ordinary or everyday.